Nanostructured crystallization of casting alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Crystallization of casting alloys has been shown to be a nanostructured process. Microcrystals of phases in the temperature range of liquidus and solidus, during eutectic and peritectic reactions, are formed from nanocrystals of components A and B of alloys, their free atoms and atomic complexes. Microcrystals of primary austenite and austenite-graphite eutectics during crystallization of cast iron, microcrystals of austenite and δ-ferrite during crystallization of steel are formed as a result of nanostructural reactions from elementary nanocrystals of iron and graphite, free atoms of iron and graphite, iron-carbon complexes. Primary and eutectic microcrystals of silumin are formed from elementary nanocrystals of aluminum and silicon, free atoms of aluminum and silicon, aluminum-silicon complexes.